Diffusion enhancement in on/off ratchets - Germs, Wijnand Chr.; Roeling, Erik M.; IJzendoorn, L. J. van; Janssen, R. a. J.; Kemerink, Martijn (Applied physics letters, 2013)
We show a diffusion enhancement of suspended polystyrene particles in an electrical on/off ratchet. The enhancement can be described by a simple master equation model. Furthermore, we find that the diffusion enhancement can be described by a general curve whose shape is only determined by the asymmetry of the ratchet repeat unit. The scaling of this curve can be explained from an analytical expression valid for small off-times. Finally, we demonstrate how the master equation model can be used to find the driving parameters for optimal particle separation.
Gesehen am 12.12.2019